Pengaruh Model Project Based Learning (PJBL) Berbantuan Media Bahan Bekas Terhadap Pemahaman Konsep Dan Literasi Matematika Siswa Sekolah Dasar - Haryadi, Herjan; Mudzakkir, Ahmad (Media Pendidikan Matematika, 2024)
The low understanding of students' mathematical concepts in mathematics learning makes it difficult for students to understand mathematics learning, especially in terms of understanding story problems and understanding the concept of counting. Understanding mathematical concepts and literacy, especially in understanding story problems and the concept of counting in elementary schools can be implemented through a learning process that can provide student involvement such as the project-based learning (PJBL) model. This study aims to determine the influence of the project-based learning (PJBL) model on students' understanding of mathematical concepts and literacy in elementary schools. The research method uses a quantitative approach with a quasi-experimental type. Data collection techniques use tests, observations and documentation. Data analysis uses descriptive statistics, classical assumption tests, and hypothesis testing using the Multivariate Analysis Of Variance (Manova) test and t-test. The results of this study are (1) There is an influence of the project-based learning (PJBL) model assisted by used material media on the understanding of mathematical concepts and literacy of grade 3 SDN 3 Kuripan or Ha is accepted. Where the Manova F-count test value is 19.427 with a significance level value of 0.000 or less than 0.05 (2) There is an influence of the Project Based Learning (PJBL) Model assisted by used material media on the understanding of mathematical concepts of class 3 SDN 3 Kuripan, where the t-test results are 9.558 with a significance level value of Asymp. Sig. (2-tailed) 0.000 less than 0.05 and (3) There is a Project Based Learning (PJBL) Model assisted by used material media on mathematical literacy of class 3 SDN 3 Kuripan. With a t-test value of 9.558 and a significance level value of Asymp. Sig. (2-tailed) 0.000 less than 0.05